Vol 14 No 1 (2020) DETERMINAN VARIABEL YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO PADA PERUSAHAAN-PERUSAHAAN YANG TERGABUNG DALAM LQ45 - Achmad Jaelani Achmad Jaelani (Cakrawala Akuntansi & Manajemen, 2020)
The purpose of this study is to conduct an analysis of factors affecting the company’s payout ratio dividend incorporated in LQ45 which listed on the Indonesia Stock Exchange. Seven independent variables to predict the simultaneous influence of the dividend payout ratio were tested using multiple regression analysis of the profitability (ROE), and debt to equity ratio. This study used a sample of companies incorporated in LQ45 during the period 2009-2011, which generates 45 observations. The result of the analysis indicate that there are only four independent variables have significant influence on dividend payout ratio that are free cash floq, growth, cash position and debt to equity, where as the other three variables had no significant effect.This study also indicates that the variable divident payout ratio can be explained by the seven independent variables by 71,6% while 28,4% can be explained by other variables.